Validação do reprocessamento de cateteres cardíacos angiográficos: uma avaliação da funcionalidade de integridade - Thabata Coaglio Lucas (2008)
The reprocessing of dental and medical devices due to chemical residuous from the process ofcleaning and sterilization that interact with the polymers can gradually deteriorate thecatheters, changing their mechanical, related to functionality of the materials (lost ofresistance to traction) and chemical, related to molecular and micro-structural integrity of thepolymer chain (changes in the molecular structure of polymers, micro-fissures, roughness andsurface imperfections) properties. These changes can imply in the occurrence of adverseevents in patients, raising questions in relation to an ethical and safe practice of the institutionand its professionals. This study is aimed at validating the reprocessing of cardiacangiographic catheters in relation to their characteristics of functionality and integrity. It wasan experimental, comparative and controlled research that conducted in the labs ofBioengineering and Polymers and Composites Engineering of the Minas Gerais FederalUniversity. The functionality of the catheter was evaluated by a traction test and the integrityby the Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy(SEM). The results showed a tendency of reduction of the deformation average in the maximstrength and an increase in the rigidity connected to the addition of the number ofreprocessing (p<0.05). The modifications of mechanical properties were more evident in thefifth reprocessing, though the catheters had kept a ductile behaviour up to the ninthreprocessing. The FTIR showed that the increase of the number of bounded carboniles ineach increasing of the number of reprocessing was responsible for an oxidative degradationby crosslinking (p<0.001). The micrographs from the SEM revealed an increase in theroughness, micro-fissures and micro-scratches in the catheters from the fourth reprocessing.This study might contribute for a sensibilization of the hospital institutions and third-partycompanies to the elaboration of protocols of reprocessing, careful inspection of dental andmedical devices and systematic surveillance of the reutilization of material recommended fora single-use. Besides that, it will give enough bases for a reflection about the reprocessingvalidates, not only by its economic relevance, but above all by an ethical, environmental, legaland assistance point of view.